ANALISIS TINGKAT KONSUMSI IKAN DI DESA ARONGAN, KECAMATAN KUALA PESISIR, KABUPATEN NAGAN RAYA - Yuli Milda Maiman; Uswatun Hasanah (Universitas Teuku Umar, 2022)
One of the government's policies in encouraging economic growth from the fishery sectoris to increase fish consumption. Arongan Village, Kuala Pesisir Subdistrict, Nagan RayaRegency is one of the villages that has quite large fishery potential. The high potential offisheries is not always accompanied by a high level of fishery products consumption aswell. In this regard, accurate information is needed regarding the level of fishconsumption. In this study, the level of fish consumption was divided into threecategories, namely low, medium and high consumption levels. This study aimed todetermine the level of fish consumption and analyze the pattern of relationships of factorsthat influence the level of marine fish consumption in the Arongan Village, Kuala PesisirDistrict, Nagan Raya Regency. The analytical method used was descriptive quantitativemethod and multinomial logistic regression. The data used in this study was primary dataobtained through observation and questionnaires by taking samples based on randomsampling. There were 80 respondents. The results showed that there were 36.25% highfish consumption levels, 51.25% moderate fish consumption levels, and 12.5% low fishconsumption levels. It was also found that the variables of education, occupation, andincome simultaneously did not have a significant effect on the level of fish consumption,while partially, the variables of education, occupation and income did not have asignificant effect on the level of marine fish consumption.